Mixed bivalent transition metal complexes of 1,10-phenanthroline and 2-aminomethylthiophenyl-4-bromosalicylaldehyde Schiff base: Spectroscopic, molecular modeling and biological activities - Aljahdali, Mutlaq Shedeed; El-Sherif, Ahmed Abdou; Hilal, Rifaat Hasan; Abdel-Karim, Abeer Taha (European Journal of Chemistry, 2013)
Mixed ligand complexes of M(II) M = Cu(II), Ni(II), Co(II) and Zn(II) with 1,10-phenanthroline (1,10-Phen) and Schiff base namely 2-aminomethylthiophenyl-4-bromosalicylaldehyde (ATS) have been synthesized. These metal chelates have been characterized by elemental analyses, IR, 1H NMR, solid reflectance, magnetic moment and molar conductance. Spectral data showed that the 1,10-phenanthroline act as neutral bidentate ligand coordinating to the metal ion through two nitrogen donor atoms and Schiff base (ATS) acts as monobasic bidentate coordinating through through azomethine-N and phenolic-oxygen groups. The geometry of the studied M(II) complexes has been fully optimized. The metal chelates have been screened for their antimicrobial activities using the disc diffusion method against different selected types of bacteria and fungi. In vitro antitumor activity assayed against two human cell lines colon (HCT116) and larynx (HEP2) cancer cells. Solution equilibrium studies were also investigated.